Two Enraging Gifts in Egils saga - Barreiro, Santiago Francisco
Egils saga Skallagrímssonar is a long prose text composed in Iceland in the first half of the thirteenth century (c.1220-1240). It is conventionally considered as an early example of the subgenre known as Íslendingasögur, which tell stories about the early generations of inhabitants who settled in Iceland in the ninth and tenth centuries. Our goal in this article is to compare and contrast two instances of gifts present in the saga, which in both cases cause a furious reaction in the recipient. We conclude by making some remarks on the relationship between the results of our analysis and its link with the two main broad trends in the anthropology of exchange, those focusing on the strategies of the agents and those focusing on the gift as structurally determined. Fil: Barreiro, Santiago Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina